REVIEW OF MONITORING TECHNOLOGIES USED IN HYBRID PHOTOVOLTAIC SYSTEMS - TEODOR POP; RADU-DUMITRU PENTIUC; VISARION-CATALIN IFRIM; CIPRIAN BEJENAR; PAVEL ATANASOAE (Journal of Engineering Studies and Research, 2024)
In the present context, due to the increase in global energy demand and the need to reduce greenhouse gases, hybrid systems that produce electricity and heat from renewable sources have been proposed, designed and implemented. Most of the available solar energy is captured using photovoltaic systems and converted into electricity. Today's modern systems refer to combinations of photovoltaic and thermal panels (PV/T) to obtain electricity and domestic hot water, and systems consisting of photovoltaic panels with wind turbines which provides only electricity. With an optimal design, PV/T systems can provide buildings with 100% renewable electricity and heat. This is done in a more cost-effective and efficient way compared to using photovoltaic and solar thermal systems separately. The areas required to install photovoltaic systems can be reduced by using hybrid energy production systems. The introduction of a hybrid photovoltaic-wind system reduces the land area from 1.5 ha/MW to 0.4 ha/MW. Due to the influence of environmental factors affecting the functionality of hybrid systems and the need to achieve optimal performance, the development and implementation of advanced monitoring methods has become a mandatory requirement. The paper presents different methods of monitoring hybrid systems, their progress and performance.